Neurotoxic effect of Malaysian cobra venoms and neutralization by Thai's antivenoms. - Zulkifli, Nor Asyikin; Ibrahim, Zalikha; Othman, Iekhsan; Chaisakul, Janeyuth; Ismail, Ahmad Khaldun; Ahmad Rusmili, Muhamad Rusdi (2021)
Introduction: N. sumatrana and N. kaouthia are two medically important species of cobra in Southeast Asia. They are known to cause neurotoxicity symptoms. In Malaysia, systemic envenoming caused by cobra is treated using antivenoms imported from Thailand. Variations in venom in a locality could cause antivenom produced in another locality to be ineffective and increase treatment cost. Objective: Objectives of this study are to assess neurotoxic effect of Malaysian N.sumatrana and N.kaouthia and effectiveness of Thai antivenom for reversing neurotoxicity using in-vitro preparation. Methods: In-vitro neurotoxic effects of N. sumatrana and N. kaouthia crude venom were assessed by indirect stimulated chick biventer cervicis preparation. The neurotoxicity activity was determined using time for 90% reduction in twitch response (t90) and response to exogenous ACh, CCh and KCl. Neutralization was assessed using cobra antivenom and king cobra antivenom by pre-incubation of antivenom and addition of antivenom at t90. Animal ethic approval ID:IIUM/IACUC-2019(13). Results and Discussion: Both venoms were found to elicit concentration-dependent effect and reduced response to exogenous agonists in the chick biventer cervicis preparation. N. kaouthia venom was found to be more potent than N. sumatrana venom based on t90 value. Both venoms contain postsynaptic neurotoxin and myotoxin based on ACh, CCh and KCl responses.In the pre-incubation study, all antivenoms significantly attenuated reduction of twitch compared to venom alone but when added at t90, did not restore twitch height for Cobra Antivenom and King Cobra Antivenom. Our finding showed that neurotoxicity caused by Malaysian N.sumatrana and N.kaouthia could be differentiated using in vitro preparation and the effect can be prevented by pre-incubation using Thai’s Cobra Antivenom and King Cobra Antivenom.